RELEVANSI SISTEM PENDIDIKAN NASIONAL DENGAN PEMBARUAN SISTEM PENDIDIKAN PESANTREN - Subekti, Yusuf Agung (STAI Ma'had Aly Al-Hikam Malang, 2014)
National Education System passed by in June 11, 2003, and entered into force in July 8, 2003, had the alignment toward existing Islamic education, pesantren. Since the modernization of Islamic education system in Indonesia was launched, actually that was influenced by both the Western and the Middle Eastern. There was less number of the like the Moslem boarding school could survive. Many classical Islamic boarding schools variously changed. Some totally evicted by the modern education system and other adopted any methodology of the modern education system. The last received very limited changes of modernization to survive. They changed by revising the system and methods. This article views National Education System as a reference in developing the Islamic education, pesantren as its renewal covers discrimination abolishment on education and justifies the relevance.